Polycrystalline silicon field emitters - Boswell, E; Huq, SE; Huang, M; Prewett, P; Wilshaw, P (1996)
Field emission of electrons from polycrystalline silicon micropoint emitters has been investigated. Two process routes, wet and dry etching, were used to form emitters, and their morphologies were compared using a transmission electron microscope (TEM). TEM micrographs of the wet-etched polysilicon structures show the presence of many individual grains at the tip. Arrays were easily manufactured, using the wet-etch process, to form sharp conical micropoints. However, the dry-etch process did not allow the formation of sharp tips. Field emission current-voltage data was collected from the wet-etched polycrystalline emitters immediately after etching and showed their emission characteristics to be similar to single crystal silicon emitters. Oxidation sharpening had little effect on the field emission characteristics. (C) 1996 American Vacuum Society.